CHALLENGES OF OPERATIONAL EFFICIENCY FACED BY SELECTED OIL AND GAS EXPLORATION ORGANIZATIONS IN KENYA - Mobutu, James Okal; Nzulwa, Dr Joyce (International Journal of Strategic Management, 2021)
Purpose: the purpose of the study is to assess the challenges of operational efficiency faced by selected oil and gas exploration organizations in Kenya. Methodology: This study applied descriptive research design and employ exploratory research to explore the variables. The population of interest in this study comprised of 37 selected entities involved in exploration. The study adopted a structured questionnaire. The study data was also analyzed using descriptive statistics and presented in tables and charts. Frequencies and percentages was used to explain data sets and results. Inferential statistics were drawn based on findings of the descriptive statistics. Findings: Results indicate that operational efficiency would rise by 0.116 with every unit positive increase in community issues provided that other factors (infrastructure issues, local content, and security) are constant, and the statistic is insignificant at 95% confidence level (p=0.130). The application of infrastructure issues would lead to an increase in operational efficiency by factor of 0.049 at p= 0.620 should other factors be held constant. Holding other factors (community issues, infrastructure issues and security) constant, a unit increase in local content would lead to a 0.856 increase in operational efficiency (p<0.001). Lastly, a unit increase in security would lead to a 0.132 increase in operational efficiency these statistics being significant (p<0.01) at 95% of significance. Unique Contribution to Theory Practice and Policy: Operational management acts are measured by an organization efficiency performance metrics. Given that operations management is evolving into a service activity, operational managers need to visit research papers to ascertain what are the contributors to their performance metrics. This study has attempted to demystify the notion that all the independent variables have equal probability of affecting operational efficiency and instead has instead discovered that there exists a positive correlation and each independent variable has a hierarchical contribution towards the score of an operational efficiency performance metric.